Spectrophotometric Analytical method for Determination the Drug Compound Salbutamol by using Prussian blue Complex (Baghdad Science Journal, 2025)
This research aims to develop new spectrophotometric analytical method to determine drug compound Salbutamol by reaction it with ferric chloride in presence potassium ferricyanide in acid median to formation of Prussian blue complex to determine it by uv-vis spectrophotmetric at wavelengths rang(700-750)nm .Study the optimal experimental condition for determination drug and found the follows:1- Volume of(10M) H2SO4 to determine of drug is 1.5 ml .2- Volume and concentration of K3Fe(CN)6 is 1.5 ml ,0.2% .3- Volume and concentration of FeCl3 is 2.5ml , 0.2%.4- Temperature has been found 80 .5- Reaction time is 15 minute .6- Order of addition is (drug + K3Fe(CN)6+ FeCl3 + acid) .Concentration rang (0.025-5 ppm) , limit detection(0.02)ppm . The method was applied successfully to determine the drug in tablet pharmaceutical preparation by use direct calibration curve and standard addition curve the recovery was 98.5% .